PENGARUH ELECTRONIC WORD OF MOUTH TERHADAPKEPUTUSAN MENGINAP DI HOTELDI KOTA BANDUNG - Kresna Binawan, - (2021)
Kresna Binawan (1501952), "The Effect of Electronic Word of Mouth on The Decisions to Stay at a Hotel in the city of Bandung (a survey of guests who decided to stay and at the same time gate information through online reviews in the city of Bandung) under the guidance of Dr. Vanessa Gaffar, SE., Ak., MBA and Dewi Pancawati N. S.Pd., M.M. This study aims to figure out the effect of electronic word of mouth on purchased decisions on hotel in Kota Bandung. The research method used is descriptive verification. Data technique that use for this research is google form. Population of this study were guests who decided to stay and at the same time gate information through online reviews in Kota Bandung. The sampling technique was based on systematic random sampling of 100 respondents. Statistical analysis used in this research is multiple regression analysis techniques with SPSS 20 for Windows application. This research scale use the Likert scale. Based on the test, it was found that the simultaneous electronic word of mouth had a significant effect on Purchased Decisions. Results of this study indicate that the level of electronic word of mouth is in the high category and Purchased Decisions is in the high category. And electronic word of mouth has a positive effect on Purchased Decisions. Partially, the eight dimensions, Source expertise, source trustworthness, receiver expertise, volume of ewom, valence of ewom, type of ewom, nature of the product and homophily have a significant effect on Purchased Decisions. Keywords: Electronic word of mouth, Decisions to Stay, Hotel in Bandung